2021
DOI: 10.1186/s12906-020-03190-1
|View full text |Cite
|
Sign up to set email alerts
|

Vochysia tucanorum Mart. butanol fraction presents antitumoral activity in vivo and prevents the installation of cachexia in solid Ehrlich tumor model

Abstract: Background Cancer is a multifactorial disease caused by uncontrolled proliferation of cells. About 50–80% of cancer patients develop cachexia, a complex metabolic syndrome associated with an increase of mortality and morbidity. However, there are no effective therapies in medical clinic for cancer cachexia. Vochysia tucanorum Mart. is a common three of the Brazilian “Cerrado”. The butanolic fraction of V. tucanorum (Fr-BuVt), very rich in triterpenes with various biological activities, might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It is a key factor in autophagy induction and plays a vital role in cell growth, proliferation, autophagy, and survival. Promising results have been seen from testing mTOR inhibitors against tumor cells [20]. We found that ligustilide significantly reduced the ESC-induced elevation in the expression of mTOR.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is a key factor in autophagy induction and plays a vital role in cell growth, proliferation, autophagy, and survival. Promising results have been seen from testing mTOR inhibitors against tumor cells [20]. We found that ligustilide significantly reduced the ESC-induced elevation in the expression of mTOR.…”
Section: Discussionmentioning
confidence: 66%
“…mTOR functions as a serine/threonine protein kinase that regulates cell growth, cell proliferation, cell motility, cell survival, protein synthesis, autophagy, and transcription [20]. In ESC, mTOR had elevated gene expression and protein levels compared to the control group.…”
Section: Effect Of Ligustilide On Mtormentioning
confidence: 99%
“…According to Machado and Melo Júnior 25 , weight parameters, such as the weight of tumors and variations in body mass, are extremely valuable to monitor the effects of antineoplastic drugs. Cancer cachexia is a multifactorial syndrome that affects the prognosis of the disease in 50% of patients 26 , leading to a progressively negative energy balance that impairs the functioning of the body and affects various organs, such as the liver and brain 27 . Muscle, lipids, and carbohydrates are used by the body, and by the tumor itself, as substrates for hypercatabolism, causing weight loss, the main characteristic of the syndrome 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cachexia is a multifactorial syndrome that affects the prognosis of the disease in 50% of patients 26 , leading to a progressively negative energy balance that impairs the functioning of the body and affects various organs, such as the liver and brain 27 . Muscle, lipids, and carbohydrates are used by the body, and by the tumor itself, as substrates for hypercatabolism, causing weight loss, the main characteristic of the syndrome 27 . Solid Ehrlich tumor is an efficient model for the study of the effects of cachexia, reproducing the systemic proinflammatory effects that generate skeletal muscle loss and lipolysis 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this versatility, the advantages of the model include fast tumor growth and high rates of tumor occurrence after transplantation ( 60 ). The antineoplastic potential of a wide variety of substances has already been tested, including probiotics, polysaccharides, oligosaccharides, spices, plant extracts, isolated compounds, seaweed, off-label drugs alone or in combination with routine anticancer drugs, and countless variations of formulations, including nanoparticles ( 8 , 16 - 19 , 61 - 65 ). Table 2 shows some applications of solid and liquid models of Ehrlich carcinoma in preclinical studies.…”
Section: Research Applications Of Ehrlich Tumor Modelmentioning
confidence: 99%